2008
DOI: 10.1108/13665620810860477
|View full text |Cite
|
Sign up to set email alerts
|

Engaging workers in simulation‐based e‐learning

Abstract: PurposeThe purpose of this paper is to evaluate learners' attitudes to the use of simulation‐based e‐learning as part of workplace learning when socially situated interaction and blended learning are specifically included in the instructional design.Design/methodology/approachResponses to a survey questionnaire of 298 sales personnel were collected and analysed. Additionally, quantitative and qualitative data from 37 sales directors were obtained to further address the research question.FindingsIt was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…When the research in this area is evaluated, it emerges that blended learning is far more likely to be successful than the technology-assisted single-mode delivery of training (e.g. providing web-based content as the total offering), reportedly because of individual learning styles [70], but conceivably also because of the limitations of any one method or tool in isolation.…”
Section: Instructional Designmentioning
confidence: 96%
“…When the research in this area is evaluated, it emerges that blended learning is far more likely to be successful than the technology-assisted single-mode delivery of training (e.g. providing web-based content as the total offering), reportedly because of individual learning styles [70], but conceivably also because of the limitations of any one method or tool in isolation.…”
Section: Instructional Designmentioning
confidence: 96%
“…The use of simulations and games has a significant positive correlation in enhancing the students learning and knowledge; moreover developing their skills such as team working and communication [9], [10]. Despite the fact that there is a future for simulation games, there is a need for more corporation between industry and academia to create better simulation products [11].…”
Section: A General Simulation Studiesmentioning
confidence: 99%
“…It has been applied to a variety of settings such as healthcare (e.g., Rosen et al, 2010), the military (e.g., Freeman & Cohen, 1996), management education (e.g., Salas, Wildman, & Piccolo, 2009), and customer service (e.g., Slotte & Herbert, 2008). Empirical research has largely focused on comparing SBT to other training approaches, assessing its effectiveness in different contexts or for training different KSAs, and examining instructional features that render it more or less effective.…”
Section: Is Simulation-based Training Effective?mentioning
confidence: 99%
“…After undergoing SBT, team members had shared beliefs in their abilities to perform as a team, showed increased levels of motivation and readiness, performed at target levels, and had favorable reactions to the training programthey were satisfied with it and believed it was useful for improving their performance. Representing other contexts, Freeman and Cohen (1996) used SBT to improve the decision-making processes of Navy teams, and Slotte and Herbert (2008) found that it facilitated customer service in a sales environment. These examples highlight the value of SBT not only for use in variety of settings, but also for training a variety of competencies.…”
Section: Is Simulation-based Training Effective?mentioning
confidence: 99%